Amphiphilic copolymers of dimethyl aminoethyl methacrylate and methyl methacrylate with controlled hydrophilicity for antialgal activity. Issue 5 (30th August 2021) - Mushtaq, Shehla; Abbas, Muhammad Asad; Nasir, Habib; Mahmood, Azhar; Iqbal, Mudassir; Janjua, Hussnain A.; Malik, Qamar; Ahmad, Nasir M.
Abstract: Biofouling due to algae mass attachment has detrimental effects on the performance and economy of many manufacturing processes. In consideration of this, present research is focused to mitigate such effect through the development of environmentally benign active antialgal cationic amphiphilic copolymers of poly(2‐(dimethylamino)ethyl methacrylate) (PDMAEMA) and methyl methacrylate (MMA). The copolymers compositions were synthesized to tailor various characteristics to control surface biofilm formation and antialgal activities were determined through suspension assay. Biofilm formation of Dictyosphaerium sp . algae on the synthesized copolymers of different surface energies was ascertained by measuring chlorophyll A content and percent adhesion of algae. The copolymers antialgal performance enhanced with increase in PDMAEMA concentration as it exhibited the lowest contact angle as well as adhesion and minimum chlorophyll A contents. Algal adhesion on the surface of materials was also observed by optical microscopy. The copolymers with higher concentration of DMAEMA resulted in greater hydrophilicity which exhibited low adhesion of Dictyosphaerium algae due to possibility of stronger hydration effect and wettability as evident from their lower water contact angle. The developed benign cationic polymers of PDMAEMA and PMMA with varying compositions can lead to important breakthrough in the subject area of antialgal research in several manufacturing processes. Abstract :